Electroencephalogram Signatures of Agitation Induced by Sevoflurane and Its Association With Genetic Polymorphisms - Zhao, Shuai; Han, Linlin; Zhou, Ruihui; Huang, Shiqian; Wang, Yafeng; Xu, Feng; Shu, Shaofang; Xia, Leiming; Chen, Xiangdong (Frontiers in Medicine, 2021)
Background: Volatile anesthetic-induced agitation, also called paradoxical excitation, is not uncommon during anesthesia induction. Clinically, patients with agitation may lead to self-injury or disrupt the operative position, increasing the incidence of perioperative adverse events. The study was designed to investigate clinical features of sevoflurane-induced agitation and examined whether any genes polymorphisms can potentially be used to predict agitation. Methods: 176 patients underwent anesthesia induction with sevoflurane were included in this study. Frontal electroencephalogram (EEG), electromyography (EMG) and hemodynamics were recorded continuously during anesthesia induction. DNA samples were genotyped using the Illumina Infinium Asian Screening Array and the SNaPshot technology. Genetic association was analyzed by genome-wide association study. Logistic regression analysis was used to determine the role of variables in the prediction of agitation. Results: 25 (14.2%) patients experienced agitation. The depth of anesthesia index (Ai index) (p<0.001), EMG (p<0.001), heart rate (HR) (p<0.001) and mean arterial pressure (MAP) (p<0.001) rapidly increased during the agitation. EEG exhibited a shift towards high frequencies with spikes during agitation. The fast waves (alpha and beta) were more pronounced and the slow rhythms (delta) were less prominent during the occurrence of agitation. Moreover, 3 SNPs in the methionine synthase reductase (MTRR) gene that were correlated to the susceptibility to agitation (p < 5.0 × 10−6). Carrying rs1801394 A>G (odds ratio 3.50, 95% CI 1.43-9.45) and/or rs2307116 G>A (3.31, 1.36-8.95) predicted a higher risk of agitation. Conclusions: Our present study suggests that the agitation/paradoxical excitation induced by sevoflurane is characterized as increases in Ai index, EMG, HR and MAP, and the high frequency with spikes in EEG. Moreover, our results provide preliminary evidence for MTRR genetic polymorphisms, involving folate metabolism function, may be related to the susceptibility to agitation. Clinical trial number and registry URL: ChiCTR1900026218; http://www.chictr.org.cn/showproj.aspx?proj=40655